Mereduksi Trauma Akibat Bencana Gempa Bumi Menggunakan Pendekatan Cognitive Behavioral Therapy - Maulida, Dina; Fitriyani, Nina (Universitas Budi Luhur, 2023)
An earthquake is a vibration or shaking that occurs on the surface of the earth due to the movement or release of energy from within the earth. Trauma is a condition in which an individual is disturbed both physically and psychologically due to an event that is quite frightening and makes the individual unable to control his thought patterns. Through the Cognitive Behavioral Therapy (CBT) approach, individuals who are traumatized by the earthquake can improve cognitive aspects (mindsets) that are distorted due to the events they experience, so that individuals can change their mindsets to be more positive, while the behavioral aspects (behaviors) teach individuals to change the way you react to situations and how to respond to them in a healthier and more productive way. This article aims to discuss the cognitive behavioral therapy approach in reducing the trauma of the earthquake disaster. Writing this article aims to discuss the concept of a cognitive behavioral therapy approach to reduce trauma due to the earthquake disaster. This research is a library research, which is a method of collecting data by understanding and studying theories from various literature related to cognitive behavioral therapy in reducing post-earthquake trauma.